What's wrong with me? the frustrated patients' guide to getting an accurate diagnosis - Dannheisser, Lynn M. (McGraw-Hill, 2005)
A helpful guide to self-diagnosis shows readers how to determine their own unexplained ailments by learning how to create a "partnership" with their doctors, search for clues on the Internet, and deal with chronic pain, insomnia, and stress symptoms. Original. 15,000 first printing.